Holotranscobalamin Is a Useful Marker of Vitamin B12 Deficiency in Alcoholics. (12th March 2012) - Fragasso, Alberto; Mannarella, Clara; Ciancio, Angela; Scarciolla, Oronzo; Nuzzolese, Nicoletta; Clemente, Rocco; Vitullo, Eustachio; Sacco, Andrea
Abstract : Background . Measurement of serum cobalamin (Cbl) levels is the standard investigation for assessing vitamin B12 deficiency. Falsely increased values of Cbl can be caused by alcoholic liver disease. Measurement of total vitamin B12 serum levels might be misleading in alcoholics, because a tissue metabolic deficiency is possible even with normal serum Cbl levels. Holotranscobalamin (HoloTC), the Cbl metabolically active fraction, is considered as a better index of vitamin B12 deficiency. Methods . For assessing vitamin B12 status, we evaluated 22 adult alcoholic male patients by measuring in parallel serum Cbl, serum folate and red blood cell folate levels, HoloTC levels by the AxSYM assay. Results . HoloTC values were reduced in 3 alcoholics with borderline-low Cbl values. Significant positive correlations were found between serum Cbl and HoloTC levels, serum Cbl and gamma-glutamyl transpeptidase (GGT). Conclusion . HoloTC measurement is a useful option for assessing vitamin B12 status in alcoholics, particularly in the subjects with borderline Cbl values and may be considered an early marker of vitamin B12 deficiency.